Enhancing Clinical Communication through AI-Powered Recording and Analysis: A Multi-Center Study of Scribr AI Implementation - Saroj Kumar Rout (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article examines the implementation and effectiveness of Scribr AI, an artificial intelligence-powered system designed to enhance doctor-patient communication through automated recording, transcription, and multilingual support in clinical settings. The article evaluates the platform’s impact on clinical documentation, patient comprehension, and longitudinal care management across multiple healthcare facilities. Through a comprehensive article analysis of system usage, patient engagement, and healthcare provider feedback, the article demonstrates significant improvements in communication accuracy, patient understanding, and clinical workflow efficiency. The findings indicate that AI-enabled recording and translation systems can effectively bridge language barriers, enhance patient recall of medical instructions, and support precision medicine through detailed documentation of health histories. Additionally, the study reveals notable benefits for chronic care patients through improved tracking and accessibility of historical health data. These results suggest that AI-powered communication tools can play a crucial role in modernizing healthcare delivery while addressing persistent challenges in doctor-patient communication and medical documentation. The findings have important implications for healthcare institutions seeking to improve patient engagement, reduce communication barriers, and enhance the quality of clinical documentation.